2022
DOI: 10.17977/um016v6i12022p023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variation of SiC Mass Fraction on Mechanical Properties of Al-SiC Composite Using Stir Casting Method

Abstract: Al-SiC is a composite composed of AA6061 as a matrix and SiC as a reinforcement particle. The variation of mass added will affect the mechanical properties of the composite because Al-SiC is hardenable, which means that its mechanical properties can be improved by adding the reinforcement component. However, an excessive portion of SiC leads to a decrease in mechanical properties. The purpose of this study was to find the optimal composition of the addition of SiC into the aluminium matrix to gain maximum tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…With the addition of copper, the hardness value of aluminum silicon (Al-Si) alloy will increase with the amount of copper. The greater the amount of copper added to the alloy, the greater the hardness value [7].…”
Section: Fig 4 Results Of Hardness Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…With the addition of copper, the hardness value of aluminum silicon (Al-Si) alloy will increase with the amount of copper. The greater the amount of copper added to the alloy, the greater the hardness value [7].…”
Section: Fig 4 Results Of Hardness Testsmentioning
confidence: 99%
“…The research team also conducted previous research on a similar topic and found that adding 8% Mg could achieve a maximum hardness of 87.67 HRB. In contrast, an ultimate tensile strength of 174.26 MPa was achieved with the addition of 5% Mg [11]. Further investigation revealed an ultimate tensile strength of 196.36 MPa and a hardness of 66 HRF (Rockwell Hardness Scale F) for a composition of 10% SiC [7].…”
mentioning
confidence: 92%
See 2 more Smart Citations